Bioavailability of trace metals and rare earth elements (REE) from the tropical soils of a coal mining area - Galhardi, Juliana A.; Leles, Bruno P. [UNESP]; Mello, Jaime W. V. de; Wilkinson, Kevin J. (Elsevier B.V., 2020)
In order to assess the environmental risks related to mining activities in Southern Brazil, the transfer of trace metals and rare earth elements (REE) from soils to soybeans was evaluated in a U-rich area associated with coal mining. In some samples, As, Ba, Co, Cu and Ni were higher than the guidelines proposed by the Brazilian environmental agency. Soil, coal, ash, tailings and soybean were systematically sampled so that the chemical fractionation/speciation of the elements could be related to their bioavailability. In addition to total concentrations quantified by ICP-MS after microwave digestion, elemental measurements were made following different evaluations of the bioavailable metal, including chemical extractions (10 mM Ca(NO3)(2) and 3-step sequential extraction), diffusive gradient in thin films technique (DGT) and chemical modeling (WHAM-free ion). Lower pH and higher clay and organic matter content were reflected by higher metal assimilation by the plants, especially by the roots and leaves. The bioaccumulation factor (BF) was generally higher for the leaves (e.g. Cu, Mn, Sr, Zn, Ba, REE with exception of Tm and Yb) and roots (e.g. Cd, Th and U). The results revealed that for Ba, Cd, Sr, Pb, U and most of the REE, the free ion concentration was strongly correlated with the metal content in the plants, especially for the grains. Values obtained by DGT were also correlated with the bioavailable portion of Ba, Mn, Sr, Zn, Pb, U and REE. Measurements obtained from Ca extractions correlated well with the bioavailable metals for Ba, Cd, Sr, Rb, Pb and Th. The free or extractable metal fractions gave much better correlations of the bioavailable fractions than did the total metal concentrations from the soils, especially for the REE. The paper validates some simplified means of estimating the risks associated with metals and REE in tropical soils affected by mining activities. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Bioaccumulation; Trace metals; Rare earth metals; Mining Tropical soils; Metal mobility